Valor percebido: um estudo com clientes bancários pessoas físicas de bancos e fintechs de uma região do interior do Rio Grande do Sul - Moraes, Patricia Paseto de (Universidade do Vale do Rio dos Sinos, 2021)
This study sought to meet the objectives of identifying the performance of fintechs, with individual bank customers located in the interior of Rio Grande do Sul, identifying the perception of the bank customer about the new entrants of the financial market and the expansion and digital transformation movements of the banking market, at the same time composing a comparative diagnosis between fintech and traditional bank customers, based on variables related to tangibility, trust / credibility, promptness / understanding, security / guarantee, empathy. The survey was conducted with individual customers at one of the largest traditional institutions in Brazil and worldwide. The data were collected through a quantitative research, with customers of a cooperation network of branches of the researched bank, which has similar cultural and economic characteristics, an electronic survey using as a base the Servqual Scale of Parasuraman, Zeithaml and Berry (1985), which measures the difference between customers' expectations and perceptions. The collected data were treated through statistical analysis using SPSS, through the generation of graphs and comparatives. The results obtained demonstrate that the perceived value in relation to the fintechs and traditional bank has practically similar indices in the perception of customer satisfaction, in the surveyed public, however, some items present great disparity between themselves, which can be strategic points of reflection for the players of the financial market. Finally, it was noticed that the digital transformation caused by the last global financial crisis, by technological advances and, more recently, by the pandemic of COVID-19, accelerated the transformation of the financial sector and, above all, the profile of the current banking consumer, such themes were addressed in the present work and it is expected to contribute to future reflections.
Keywords: Fintechs; Sistema financeiro nacional; Inovação no segmento financeiro; Valor percebido; Consumidor bancário; National financial system; Innovation in the financial segment; Perceived value; Banking consumer; ACCNPQ::Ciências Sociais Aplicadas::Administração